MANIFESTATIONS OF DYSTROPHY IN THE PERIODONTIUM. CLINICAL AND ULTRASTRUCTURAL STUDY - Hrynovets, V.S.; Makejev, V.F.; Ripetska, O.R.; Deneha, I.S.; Buchkovska, A.Y.; Strus, Kh.I.; Chelpanova, I.V. (World of Medicine and Biology, 2022)
Dystrophic changes of all periodontal structures and teeth in patients with periodontitis and generalized periodontitis were investigated in the study. Characteristic signs of the gums’ pathological contour, as well as other clinical and radiological features of dystrophy differ in patients with periodontitis and generalized periodontitis and contribute to the improvement of their differential diagnosis. Ultrastructural examination of the patients’ gums with periodontitis revealed disseminated microthrombosis, mucoid edema and fibrinoid transformation of intermediate connective tissue, and coagulation-dystrophic changes in periodontal tissues and cells.